The problem of damage, maintenance and renovation in high-pressure reverse osmosis systems - Marjanowski, Jan; Sadaj, Maciej (Instal, 2021)
High pressure membrane technologies, especially reverse osmosis, are widely used in treatment of water for purposes of drinking, boilers and cooling systems and most of all in technologies of recycling process water. The selection of an appropriate RO system for a given process is equally important as its proper operation, taking into consideration maintaining of feed water quality according to manufacturer’s requirements, as well as selection of flows, pressures and suitable antiscalant. During membranes operation it is necessary to maintain them during downtime and perform periodic renovation involving chemical cleaning of membranes. Processes of fouling and scaling cannot be completely eliminated, but they can be significantly slowed down, allowing long-term, cost-effective operation while maintaining the lowest energy consumption possible and simultaneously achieving highest possible percentage of recovered water.